2014
DOI: 10.1111/jsr.12135
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acids and sleep in UK children: subjective and pilot objective sleep results from the DOLAB study – a randomized controlled trial

Abstract: Sleep problems in children are associated with poor health, behavioural and cognitive problems, as are deficiencies of long-chain omega-3 fatty acids such as docosahexaenoic acid. Theory and some evidence support a role for these fatty acids in sleep regulation, but this issue has received little formal investigation. We examined associations between blood fatty acid concentrations (from fingerstick blood samples) and subjective sleep (using an age-standardized parent questionnaire) in a large epidemiological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
55
0
11

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(72 citation statements)
references
References 43 publications
(64 reference statements)
6
55
0
11
Order By: Relevance
“…Pathway analyses of these genes using MAGMA 38 and Pascal 39 indicated enrichment of pathways including striatum and subpallium development, mechanosensory response, dopamine binding, catecholamine production, and long-term depression ( Figure 2a,b, Supplementary Table 23,24 ). In agreement the FADS1/2 signal, we also observe an enrichment in genes related to unsaturated fatty acid metabolism, supporting experimental and observational evidence linking polyunsaturated fatty acids with sleep and related diseases, including neuropsychiatric disorders and depression 4042 .…”
supporting
confidence: 87%
“…Pathway analyses of these genes using MAGMA 38 and Pascal 39 indicated enrichment of pathways including striatum and subpallium development, mechanosensory response, dopamine binding, catecholamine production, and long-term depression ( Figure 2a,b, Supplementary Table 23,24 ). In agreement the FADS1/2 signal, we also observe an enrichment in genes related to unsaturated fatty acid metabolism, supporting experimental and observational evidence linking polyunsaturated fatty acids with sleep and related diseases, including neuropsychiatric disorders and depression 4042 .…”
supporting
confidence: 87%
“…In fact, this correlation continued to be significant even when co-varying for both BDI and PSS. LC n -3 fatty acids may influence sleep quality [59-61]; and consistent with our observation, poor sleep correlated with the AA/DHA ratio in children [62] and with lower EPA and DHA levels in depressed inpatients [63]. It is thus possible that fatty acid supplementation can also improve sleep [60, 64].…”
Section: Discussionsupporting
confidence: 83%
“…However, the authors cautiously concluded that DHA supplementation in comparison with placebo consumption may lead to better sleep according to both subjective parental data and objective data gathered by Actigraph measurements (Montgomery, Burton, Sewell, Spreckelsen, & Richardson, 2014). …”
Section: Fat Intake and Sleepmentioning
confidence: 99%